Use of the Manufacturing Execution System in Practice: Understanding the end Users and the Acceptance of the System - Innecco, Rodrigo Menezes; Martins, Henrique Cordeiro; Gonçalves, Carlos Alberto (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose – this paper aims to examine the factors that affect the acceptance and use of the Manufacturing Execution System from the point of view of end users, using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Theoretical framework - The technology acceptance model is based on principles adopted in the attitude paradigm of psychology, which specifies how to measure the relevant attitudinal components of behavior; distinguishes beliefs and attitudes and specific as external stimuli, the objective characteristics of an attitude object, are causally linked to beliefs, attitudes and behavior. Design/methodology/approach - Data were collected by the survey method, using the seven-point Likert scale. The approach was quantitative, using the Structural Equation Modeling technique, using SPSS V.25 software. Findings - The findings of this study showed that the Facilitating Conditions influence the Usage Behavior of users of the Manufacturing Execution System. The application of multi-group comparison analysis (MGA) showed that Effort Expectancy positively influences Behavioral Intention and Social Influence also positively affects Behavioral Intention. Research, Practical & Social implications - The study brings relevant contributions in relation to aspects of understanding about the level of acceptance of MES end users in the operation phase. Originality/value - This paper makes a contribution to the literature due to the pioneering nature of the research, since no research was found in academic bases that address the use of UTAUT with the MES system. Another important contribution is that this study proposes a new model, based on UTAUT using the application of MGA. Keywords - Acceptance and Use. Technology. Manufacturing Execution System.